Peningkatan Kemampuan Membaca Teks Bahasa Jerman melalui Metode Cooperative Script - Hardianti Hardianti; Laelah Azizah; Syarifah Fathimah (Universitas Negeri Makassar, 2022)
Abstract. This study aims to determine the planning, process, and results of student learning tests using the Cooperative Script method to improve the ability to read German texts for class XII IPA 2 SMAN 2 GOWA. This type of research is a type of classroom action research which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were 32 students of class XII IPA 2 SMAN 2 GOWA. This research data consists of qualitative data and quantitative data. Qualitative data was obtained through observation and quantitative data was obtained from the results of the students' reading ability test of German text in cycle I and cycle II. The results showed that the ability to read German texts with the average score obtained by students in the first cycle was 66 and the average score in the second cycle was 80. This was proven by an increase of 14. Therefore, it can be concluded that the method Cooperative Script can improve the ability to read German texts for class XII IPA 2 SMAN 2 GOWA.Keywords: Cooperative Script Method, Reading Ability, German